Comparative analysis based on shared amplicon sequence variants reveals that cohabitation influences gut microbiota sharing between humans and dogs - Ito, Yutaro; Nagasawa, Miho; Koyama, Kahori; Ito, Kohei; Kikusui, Takefumi (Frontiers in Veterinary Science, 2024)
IntroductionThe One Health concept is a comprehensive understanding of the interaction between humans, animals, and the environment. The cohabitation of humans and pets positively affects their physical, mental, and social well-being. It is recognized as an essential factor from the One Health perspective. Furthermore, a healthy balance in the gut microbiome is essential for good health, and the changes in the gut microbiome associated with cohabitation between humans and pets could potentially affect various aspects of the health of both hosts. Therefore, elucidating the sharing of gut bacteria between humans and pets associated with cohabitation is important for understanding One Health. However, most studies have examined sharing at the taxonomic level, and it remains unclear whether the same bacteria are transferred between humans and pets, and whether they mutually influence each other.MethodsHere, microbiome analysis and shared 16S rRNA gene amplicon sequence variant (ASV) analysis were conducted before the start of cohabitation between humans and dogs, as well as at 2 weeks, 1 month, and 3 months after cohabitation.Results16S rRNA gene ASVs analysis indicated that gut microbes have been transferred between humans and dogs. The overall structure of the gut microbiota within human–dog pairs remained unchanged after 3 months of adaptation. However, 11ASVs were shared within human–dog pairs. Many shared ASVs were highly abundant within each host, and this high abundance may be considered a factor that influences bacterial transfer between hosts.DiscussionOur results provide important insights into the potential for the transfer of gut bacteria between humans and dogs. These findings are considered crucial for understanding the impact of human–dog cohabitation on various aspects of health.